PENGARUH DIRECT MARKETING, KUALITAS PRODUK, DAN KEPUASAN PELANGGAN TERHADAP MINAT BELI ULANG PADA LIVE STREAMING MARKETING SHOPEE LIVE: (Studi Kasus Pada Pengguna Aplikasi Shopee Di Universitas Teknologi Muhammadiyah Jakarta) - Wiyana, Hari; Putera, Adhitya Ibanda; Achmadi, Achmadi; Zulkarnaen, Adilla Yolanda (Yayasan Bina Internusa Mabarindo, 2024)
In the current era of business digitalization, Shopee Live has become one of the e-commerce platforms utilizing live streaming features as a marketing strategy to enhance interaction between sellers and consumers. This research aims to analyze the influence of direct marketing, product quality, and customer satisfaction on repurchase intention on Shopee Live. Repurchase intention is the primary focus as it is a crucial indicator in maintaining customer loyalty and long-term business. This study employs the Structural Equation Modeling (SEM) method to analyze data collected from 100 respondents, who are students of Universitas Teknologi Muhammadiyah Jakarta and have used Shopee Live for shopping. Validity and reliability tests are used to ensure that the research instruments are reliable and accurate in measuring the variables studied. Additionally, the R-square test is utilized to measure the extent to which the independent variables explain the variation in the dependent variable. Hypothesis testing is conducted to determine the significance of the relationships between variables. The results indicate that direct marketing has a positive but not significant effect on repurchase intention. In contrast, product quality and customer satisfaction have a positive and significant impact on repurchase intention. The implications of these findings suggest that while direct marketing is important in attracting consumer attention, product quality and customer satisfaction play a more significant role in driving repurchase decisions. Therefore, sellers on Shopee Live are advised to focus more on improving product quality and providing services that enhance customer satisfaction to increase consumer loyalty.